2022
DOI: 10.24191/bej.v19i1.15990
|View full text |Cite
|
Sign up to set email alerts
|

Pertinent Internal and External Issues in Industrialised Building System (IBS) Construction Business in Malaysia

Abstract: Industrialised Building System (IBS) construction business has emerged as one of the potential business ventures as the Malaysian construction industry is in a constant need to shift from conventional method of construction to IBS adoption aligning to Construction 4.0 Strategic Plan 2021-2025 and The National Entrepreneurship Policy 2030 (NEP 2030). In line with boosting the IBS implementation, a brief exploratory study has been conducted to validate several IBS construction business issues among IBS contracto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The present research revealed a strong and significant relationship between IBS technology practices and material management approaches. These findings are consistent with those published by Ayisy and Ghazalli (2021), Nawi et al (2019), Thomas Tarang et al, 2022, and Soon Ern et al (2017. In terms of automation in construction, recent findings by Azira et al (2020) and Kamaruddin et al (2018) indicated that automation through IBS in construction is effectively influencing Malaysia's construction performance and that automation in construction is a modern technology that could be employed to improve the efficiency and performance of all construction projects.…”
Section: Hypothesis Analysis and Discussionsupporting
confidence: 88%
“…The present research revealed a strong and significant relationship between IBS technology practices and material management approaches. These findings are consistent with those published by Ayisy and Ghazalli (2021), Nawi et al (2019), Thomas Tarang et al, 2022, and Soon Ern et al (2017. In terms of automation in construction, recent findings by Azira et al (2020) and Kamaruddin et al (2018) indicated that automation through IBS in construction is effectively influencing Malaysia's construction performance and that automation in construction is a modern technology that could be employed to improve the efficiency and performance of all construction projects.…”
Section: Hypothesis Analysis and Discussionsupporting
confidence: 88%
“…According to Alawag et al (2021), the initiatives by the government to encourage the implementation of IBS also seem not to impact the adoption rate of IBS in Malaysia significantly. Recent research done by Thomas Tarang et al (2022) highlighted that the high adoption of IBS in Malaysia still has a long way to go. The latest report from CIDB on IBS adoption in government and private projects in Malaysia in 2019 showed growth of adoption of IBS rate for public projects to 36.1% from the 2017 figure (10.7%).…”
Section: Low Adoption and Poor Performance Of Ibs In Malaysiamentioning
confidence: 99%
“…One conspicuous gap is the dearth of comprehensive studies addressing the dynamics of supply construction GDP in Malaysia. While the existing body of research delves into the industry's challenges (Dehdasht et al, 2022;Farouk et al, 2023;Waqar et al, 2023), its contributions to the national economy, and the impact of industrialised building systems (IBS) (Mohamad Kamar, Alshawi and Abd Hamid, 2009;Ali et al, 2018;Al-Aidrous et al, 2021;Ismail, 2021;Gunasagaran et al, 2022;Thomas Tarang et al, 2022), it often skirts the issue of the supply construction sector's GDP. This absence of holistic analysis, particularly concerning the sector's relationship with macroeconomic factors, presents a gap that this study aims to address.…”
Section: Introductionmentioning
confidence: 99%